How do students view online learning: an empirical study of online learning during the Covid-19 Pandemic - Tian-Zi Xu (Universidade Federal do Norte do Tocantins, 2021)
During the Covid-19 prevention and control period, the online learning became the main learning pathway for students. Meanwhile, it brings some new questions worthy to considering, such as, how was the online learning for students? How were the effects? And how did students perceive it? In order to answer those questions and gain deep understanding for online learning, the research conducted an investigation among a number of high schools in Xuzhou, Jiangsu Province, China, with an anonymous questionnaire being distributed to the students. As the main group involved in online learning, it is critical in exploring the answers and promoting developments of online learning to investigate students' views and attitudes towards the effectiveness, instruction, communication, advantages and disadvantages of online learning. The results indicate that even students could rapidly adapt to the new learning style, there are still several notable limitations, such as the lack of supervision, collective atmosphere of study, and humanity communication.